Projeto e analise da viabilidade de um sistema de geração de energia eólica submersa (Revista Interdisciplinar Pensamento Científico, 2021)
The present work deals with the theme of an article related to the generation of renewable energy through submerged sea currents. With the large fleet of offshore platforms present today, the demand for energy has increased considerably. A very convenient alternative for the generation of electric energy, in the offshore world, is the use of sea currents. In this context, this article presents a study on the implementation of submerged wind turbines fixed on the platforms. Therefore, the main objective of the work is the generation of clean energy to supply the houses (accommodation) of an offshore platform.